A Delamination Propagation Model for Fiber Reinforced Laminated Composite Materials. (19th June 2018) - Aveiga, David; Ribeiro, Marcelo L.
Abstract : The employment of composite materials in the aerospace industry has been gradually considered due to the fundamental lightweight and strength characteristics that this type of materials has. The science material and technological progress reached matched perfectly with the requirements for high-performance materials in aircraft and aerospace structures; thus, the development of primary structure elements applying composite materials became something very convenient. It is extremely important to pay attention to the failure modes that influence composite materials performances, since these failures lead to a loss of stiffness and strength of the laminate. Delamination is a failure mode present in most of the damaged structures and can be ruinous, considering that the evolution of interlaminar defects can carry the structure to a total failure followed by its collapse. The present work aims at the development of a delamination propagation model to estimate a progressive interlaminar delamination failure in laminated composite materials and to allow the prediction of material's degradation due to delamination phenomenon. Experimental data, available at literature, was considered to determine some model parameters, like the strain energy release rate, using GFRPs laminated composites. This new delamination propagation model was implemented as subroutines in FORTRAN language (UMAT-User Material Subroutine) with formulations based on the Fracture Mechanics and Continuum Damage Mechanics. Finally, the UMAT subroutine was complemented with an intralaminar model and compiled beside the commercial Finite Element (FE) software ABAQUS™.